Kajian Makroekonomi dan Bias Perilaku terhadap Keputusan Investasi dimediasi oleh Persepsi Risiko (Studi pada Usaha Menengah Kota Kendari) - Wiwiek Wijiastuty Soeparyanto; Dedy Takdir Syaifuddin; Sujono Sujono (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to (1) examine the effect of macroeconomic on investment decision of SMEs, (2) examine the effect of behavioral bias on investment decision of SMEs, (3) examine the effect of macroeconomic on the risk perception of SMEs, (4) examine the effect of behavioral bias on the risk perception of SMEs, (5) examine the effect of risk perception on investment decision of SMEs, (6) examine the risk perception as a mediator of macroeconomic influence on investment decision of SMEs, (7) examine risk perception as a mediator of the influence of behavioral bias on investment decision of SMEs.This study use a quantitative approach, with the analytical method is SEM-PLS (Structure Equation Model-Partial Least Square). The result shows that macroeconomic does not significantly affect the investment decision of SMEs, but significantly influences the risk perception of SMEs. The behavioral bias significantly affect the investment decision of SMEs, but does not significantly affect the risk perception of SMEs. The risk perception does not significantly affect investment decision of SMEs. The risk perception was proven unable to act as a mediator in the influence of macroeconomic and behavioral bias on investment decision of SMEs